1996
DOI: 10.1001/archpsyc.1996.01830120020005
|View full text |Cite
|
Sign up to set email alerts
|

Childhood-Onset Schizophrenia

Abstract: Clozapine has striking superiority for positive and negative symptoms in treatment-refractory childhood-onset schizophrenia. However, due to possibly increased toxic effects in this pediatric population, close monitoring for adverse events is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(31 citation statements)
references
References 49 publications
0
30
0
1
Order By: Relevance
“…The research question was raised because early onset of schizophrenia under age of 18 years was noticed in 50% of patients and is associated with increased severity and antipsychotic drug resistance (Kumra and Charles Schulz, 2008). Previously Kumra et al (1996) demonstrated that clozapine was superior to haloperidol. Because olanzapine has been shown to have superiority to other agents in adults, the current study was thus carried out.…”
Section: Iv: Treatmentmentioning
confidence: 99%
“…The research question was raised because early onset of schizophrenia under age of 18 years was noticed in 50% of patients and is associated with increased severity and antipsychotic drug resistance (Kumra and Charles Schulz, 2008). Previously Kumra et al (1996) demonstrated that clozapine was superior to haloperidol. Because olanzapine has been shown to have superiority to other agents in adults, the current study was thus carried out.…”
Section: Iv: Treatmentmentioning
confidence: 99%
“…In effect, several lines of evidence have been put forward: e.g., lysergic acid (LSD), an agonist of serotonin receptors, has psychotomimetic effects [Serretti et al, 1999a], and atypical neuroleptics such as clozapine and risperidone, which strongly bind to 5-HT receptors, show striking superiority over D2 antagonists (i.e., typical neuroleptics) for the treatment of schizophrenia [Kumra et al, 1996]. Tryptophan hydroxylase (EC1.14.16.4, accession no.…”
Section: Introductionmentioning
confidence: 99%
“…This would not only contravene the National Institute for Clinical Excellence guidance on atypical antipsychotics, which states that 'in individuals with evidence of treatment resistant schizophrenia clozapine should be introduced at the earliest opportunity' (National Institute for Clinical Excellence, 2002), but it would also deprive patients of a potentially unique and effective treatment. Some studies in fact suggest that its use might be worthwhile and beneficial in children and young people (Kumra et al, 1996;MacEwan & Morton, 1996;Turetz et al, 1997).…”
mentioning
confidence: 99%